Can vasohibin‐1, an endothelium‐derived angiogenesis inhibitor, be a marker of endothelial dysfunction in hemodialysis patients?. Issue 5 (19th July 2020) - Altunoren, Orcun; Kerkutluoglu, Murat; Sarısık, Feyza Nur; Akkus, Gulsum; Seyithanoglu, Muhammed; Doganer, Adem; Tutuncu Sezal, Didem; Cagrı Aykan, Ahmet; Eren, Necmi; Erken, Ertugrul; Gungor, Ozkan
Abstract: Background: Endothelial dysfunction (ED) is associated with high cardiovascular disease burden in hemodialysis (HD) patients. Vasohibin‐1, an endothelium‐derived angiogenesis inhibitor, is essential for endothelial cell survival, therefore it may be a promising marker of ED. We aimed to investigate whether vasohibin‐1 levels are associated with ED markers in HD patients. Methods: Fifty HD patients and 30 healthy controls were included in the study. As markers of ED, endothelium‐dependent flow‐mediated dilatation (FMD), carotid intima‐media thickness (CIMT), and pulse wave velocity (PWV) were examined. Serum vasohibin‐1 levels were measured with ELISA. Results: Serum vasohibin‐1 levels were low (387.7 ± 115.7 vs 450.1 ± 140.1 P = .02), FMDs' were impaired (6.65 ± 2.50 vs 10.95 ± 2.86 P < .001), PWV (7.92 ± 1.964 vs 6.79 ± 0.96 P = .01) and CIMT (0.95 ± 0.20 vs 0.60 ± 0.11 P < .001) were increased in HD patients compared to healthy controls. In regression analysis, vasohibin‐1 levels were not related with FMD, PWV, or CIMT. Conclusions: Hemodialysis patients have low serum vasohibin‐1 levels but serum levels of vasohibin‐1 did not show any significant relationship with FMD, PWV, and CIMT in HD patients. Since vasohibin‐1 acts via paracrine pathways, serum levels may be insufficient to explain the relationship between vasohibin and ED. Local vasohibin‐1 activity on tissue level may be more important instead of circulating levels.